Development of surface acoustic wave sensor for female aedes mosquito detection - Salim, Zaid T. (Institute of Nano Electronic Engineering, 2016)
The aim of this research is to develop a novel surface acoustic wave sensor for the detection of female Aedes mosquito based on the mosquito's wing beat frequency as a sensing mechanism which is in the range between 400-500 Hz. This objective will be accomplished by achieve the following to determine the wing beat frequency range of Aedes mosquito and other common mosquito species; to design and fabricate a high performance SAW device for detecting signals in the mosquito's wing beat frequency range; to examine the performance of the fabricated SAW device under lab and field conditions.